The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1063/1.2906075
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Co-doping on Microstructural, Crystal Structure and Optical Properties of Ti[sub 1−x]CO[sub x]O[sub 2] Thin films Deposited on Si Substrate by MOCVD Method

Abstract: Tii.xC0x02 thin films have been grown on n-type Si(lOO) substrates by metal organic vapor deposition (MOCVD) using titanium (IV) isopropoxide (TTIP) and tris (2,2,6,6-tetramethyl-3, 5-heptanedionato) cobalt (III) as metal organic precursors. The parameter deposition, such as: bubbler temperature of TTIP Jb(Ti) = 50°C; substrate temperature Ts = 450°C; bubbler pressure Pb(Ti) = 260 Torr; flow rate of Ar gas through TTIP precursor Ar(Ti) =100 seem (standard cubic centimeters per minute) and flow rate of oxygen g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Cobalt dopant concentrations of up to 5.77% were achieved. It was observed that the band gap was decreased with dopant concentration 88…”
Section: Metal Doping Of Titanium Dioxidementioning
confidence: 99%
“…Cobalt dopant concentrations of up to 5.77% were achieved. It was observed that the band gap was decreased with dopant concentration 88…”
Section: Metal Doping Of Titanium Dioxidementioning
confidence: 99%